Implementation of a ray tracing simulator for propagation prediction / P. Thirumaraiselvan - Thirumaraiselvan, P. (2006)
In wireless communications, understanding of the propagation channels is necessary to achieve optimum performance of a communication system, Even though direct measurements enable accurate evaluation of onsite performance, it requires a considerable amount of time and efforts. Therefore, a computer tool that could characterize the wireless channel from the building plans and material properties would be a good solution. This paper considers an approach for developing such a simulation tool using ray tracing. The simulator has been implemented in Matlab. Assuming that the scattering objects are much larger than the wavelength, the electromagnetic waves are modelled as rays, From the ray tracing results, received field strength is computed based on the theory of Geometrical Optics and Uniform Geometrical Theory of Diffraction.